Reduced seroprotection after pandemic H1N1 influenza adjuvant-free vaccination in patients with rheumatoid arthritis: implications for clinical practice. Issue 12 (22nd August 2011) - Ribeiro, Ana C M; Guedes, Lissiane K N; Moraes, Julio C B; Saad, Carla G S; Aikawa, Nadia E; Calich, Ana Luisa; França, Ivan L A; Carvalho, Jozelio F; Sampaio-Barros, Percival D; Goncalves, Celio R; Borba, Eduardo F; Timenetsky, Maria do Carmo S; et al.
Abstract : Background: Reduced response to pandemic (2009) H1N1 (pH1N1) vaccine in patients with rheumatoid arthritis (RA) was recently reported. Objectives: To evaluate the contribution of age, disease activity, medication and previous antibody levels to this reduced response. Methods: 340 adult RA patients and 234 healthy controls were assessed before and 21 days after adjuvant-free influenza A/California/7/2009 (pH1N1) vaccine. Disease activity (DAS28), current treatment and pH1N1 antibody titres were collected. Seroprotection, seroconversion and factor increase in geometric mean titre (GMT) were calculated and adverse events registered. Results: RA and controls showed similar (p>0.05) prevaccination GMT (8.0 vs 9.3) and seroprotection (10.8% vs 11.5%). After vaccination a significant reduction (p<0.001) was observed in all endpoints: GMT and factor increase in GMT, seroprotection and seroconversion rates. Disease activity did not preclude seroconversion or seroprotection and remained unchanged in 97.4% of patients. Methotrexate was the only disease-modifying antirheumatic drug associated with reduced responses (p=0.001). Vaccination was well tolerated. Conclusions: The data confirmed both short-term anti-pH1N1 vaccine safety and, different from most studies with seasonal influenza, reduced seroprotection in RA patients, unrelated to disease activity and to most medications (except methotrexate). Extrapolation of immune responses from one vaccine to another may therefore not be possible and specific immunisation strategies (possibly booster) may be needed. Clinicaltrials.gov no NCT01151644 .